Wild areas and secondary steppes of West Kazakhstan (Eurasian Journal of Ecology, 2016)
10 steppe etalon areas of secondary steppes have been selected within the West Kazakhstan. Geobotanical description of steppe etalons have been made. Steppe etalons serve as the source of seed stock for the formationof nursery garden on the experimental area.
Keywords: steppe etalon; deposit; wildland; seed stock; nursery garden